«Wunder æfter wundre»: Recounting the Marvellous in "Beowulf" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2021)
The Old English epic of Beowulf is characterised by several supernatural events in which the hero performs wondrous deeds. The most outstanding ability of the Prince of the Geats is to be able to fight dreadful beings such as sea-monsters, Grendel and its mother, and a dragon. Those prodigious contests give form to some of the main manifestations of the marvellous throughout the poem. The present study analyses the lexical incidence of recurring key-words such as “wundor” (‘astonishing thing’), “wrætlic” (‘splendid’, ‘wonder-inspiring’), and “sellic” (‘wonderful’, ‘strange’). It also aims at providing support to reading Beowulf merely as a hero with unusual strength, not as a good monster amid bad monsters.
Keywords: Beowulf; dragon; Grendel(kin); marvellous; Old English epic; water-monsters